2015 International Conference on Sampling Theory and Applications (SampTA) 2015
DOI: 10.1109/sampta.2015.7148936
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive estimation and compensation of the time delay in a periodic non-uniform sampling scheme

Abstract: High sampling rate Analog-to-Digital Converters (ADCs) can be obtained by time-interleaving low rate (and thus low cost) ADCs into so-called Time-Interleaved ADCs (TI-ADCs). Nevertheless increasing the sampling frequency involves an increasing sensibility of the system to desynchronization between the different ADCs that leads to time-skew errors, impacting the system with non linear distortions. The estimation and compensation of these errors are considered as one of the main challenge to deal with in TI-ADCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is possible to lower the price of devices by means of several samplers in parallel, and delayed alternately. Each sampler is modelled by a sequence like (7) and a set of samplers is equivalent to the PNSN (6) . To obtain a periodic sequence, the θ k have to verify the conditions θ k = θ + kT /N for some θ.…”
Section: Periodic Nonstationary Sampling Plan (Pns)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible to lower the price of devices by means of several samplers in parallel, and delayed alternately. Each sampler is modelled by a sequence like (7) and a set of samplers is equivalent to the PNSN (6) . To obtain a periodic sequence, the θ k have to verify the conditions θ k = θ + kT /N for some θ.…”
Section: Periodic Nonstationary Sampling Plan (Pns)mentioning
confidence: 99%
“…To obtain a periodic sequence, the θ k have to verify the conditions θ k = θ + kT /N for some θ. This last operation is commonly performed, it is expensive and can be avoided, staying in the PNS framework [7].…”
Section: Periodic Nonstationary Sampling Plan (Pns)mentioning
confidence: 99%
See 1 more Smart Citation
“… Hardware An example of where non-uniform sampling occurs is A/D converters. In literature, for instance [64][65][66][67], it is presented structures of A/D converters. In [67] power consumption is taken into consideration and there is demonstrated that random-sampling decreases power consumption by 25%.…”
Section:  Network Applicationsmentioning
confidence: 99%
“…In literature, for instance [64][65][66][67], it is presented structures of A/D converters. In [67] power consumption is taken into consideration and there is demonstrated that random-sampling decreases power consumption by 25%. Other examples of hardware are introduced in [14], [33], and [68][69][70].…”
Section:  Network Applicationsmentioning
confidence: 99%